2021
DOI: 10.1111/ajo.13340
|View full text |Cite
|
Sign up to set email alerts
|

Preventing harm: A balance measure for improving the detection of fetal growth restriction

Abstract: Background Increasing the detection of fetal growth restriction (FGR), while reducing stillbirth, also leads to unnecessary early intervention, and associated morbidity, for normally grown babies who are incorrectly suspected of FGR. Aims We sought to design a balance measure that addresses the specificity of FGR detection. Methods A retrospective cohort study on all singleton births ≥32 weeks gestation in 2016 and 2017 in Victoria. We compared two balance measures for the detection of FGR, defined as the prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…Adding to the clinician’s challenge is that many infants suspected of having FGR have normal growth and for these infants early intervention carries no benefit, only risk. This is because the clinical tools for detecting FGR—symphysis-fundal height measurement and ultrasound assessment of fetal size—perform poorly .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adding to the clinician’s challenge is that many infants suspected of having FGR have normal growth and for these infants early intervention carries no benefit, only risk. This is because the clinical tools for detecting FGR—symphysis-fundal height measurement and ultrasound assessment of fetal size—perform poorly .…”
Section: Introductionmentioning
confidence: 99%
“…4,5 When compounded by the risks of neurocognitive and intellectual impairment associated with FGR alone, 6,7 the attending clinician faces a challenging dilemma-either intervene early to prevent a small risk of stillbirth but potentially cause immediate and lifelong harm to the child or accept the increasing risk of stillbirth associated with prolonging the pregnancy to avoid more common neonatal and longer-term morbidities. 2 Adding to the clinician's challenge is that many infants suspected of having FGR have normal growth 2,8,9 and for these infants early intervention carries no benefit, only risk. This is because the clinical tools for detecting FGR-symphysisfundal height measurement and ultrasound assessment of fetal size-perform poorly.…”
mentioning
confidence: 99%
“…Moreover, for many years, there has been increasing concern about the high rates of obstetric intervention and the potential for iatrogenic harm [41][42][43]. Here, we provide a simple method by which SGA classification can be improved to correlate better with perinatal outcomes without inflating the proportion of pregnancies considered at risk.…”
Section: Discussionmentioning
confidence: 99%
“…General, FGR is diagnosed when fetal abdominal circumference (AC) or estimated fetal weight (EFW) for a given gestational age falls below the 10th centile or 2 standard deviations (2 SD). Some FGR pregnancies may be actually normal small for gestational age (SGA), and evidences have shown that many FGR fetuses have unexpectedly normal growth afterbirth [1][2][3][4] . However, once FGR is suspected, conducting a etiology evaluation is crucial for making informed decisions about the pregnancy and assessing the prognosis.…”
Section: Introductionmentioning
confidence: 99%